Youth unemployment and its reduction measures - Šileika, Algis; Rupšys, Valdas; Gruževskis, Boguslavas (Journal of Business Economics and Management, 2004)
The efficient use of the labour force in post‐industrial society predetermines the competitiveness of the economy and encourages social development. In this context, youth unemployment is a particularly undesirable phenomenon, reducing the efficiency of youth labour force within the level of general labour, raising social costs, and restricting social development. The position of young people on the labour market depends on a number of social, economic and demographic factors, leading to the conclusion that youth unemployment as a socio‐economic phenomenon is a particularly negative result of the interaction between these factors. The aim of the paper is to discuss the theoretical assumptions of the youth integration to the labour market and to discuss the subsequences of their unemployment. Another target of the paper is to propose the policy measures for rising economic activity of the youth. The authors of the article suggest that the youth integration to the labour market could be increased by integrated decisions based on qualified services of vocational training. First Published Online: 14 Oct 2010